Polyvinyl alcohol-based film and polarizing film using the same
By adjusting the surface hardness and elastic modulus in the polyvinyl alcohol-based film, the problems of scratches and spots in the manufacturing of polarized films are solved, and a high-quality polarized film with no display of bad spots and spots is achieved.
Patent Information
- Application Number
- CN202111114369.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-08-18
- Filing Date
- 2016-06-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2036-06-23
AI Technical Summary
The prior art is difficult to avoid scratches and color spots when manufacturing polarized films, resulting in an increase in display of bad spots and color spots of the polarized films, affecting quality.
In the nano-indentation test, a polyvinyl alcohol-based film with a hardness of 65 to 90 MPa on the surface of the film was used. By adjusting the chemical structure and manufacturing conditions of the polyvinyl alcohol-based resin, the surface hardness and elastic modulus of the film were controlled to reduce abrasions with the rollers and realize the self-healing function.
It effectively reduces scratches and color spots during polarizing film manufacturing, realizes a high-quality polarizing film without displaying bad spots and color spots, and improves manufacturing efficiency and product quality.
Smart Images

Figure BDA0003274972390000151
Abstract
Description
[0001] The present application is a divisional application of an application filed on June 23, 2016, with application number 201680022390.X and invention name “POLYVINYL ALCOHOL FILM AND POLARIZING FILM USING THE SAME”. Technical Field
[0002] The present invention relates to a polyvinyl alcohol film, and more particularly to a polyvinyl alcohol film suitable for producing a wide, long, and thin polarizing film having few display defects and color spots, and a polarizing film obtained by using the polyvinyl alcohol film. Background Art
[0003] In recent years, liquid crystal display devices have developed significantly and are widely used in smart phones, tablet computers, personal computers, LCD TVs, projectors, car panels, etc. Polarizing films are used in the above-mentioned liquid crystal display devices. As polarizing films, films formed by adsorbing iodine or dichroic dyes on polyvinyl alcohol-based films and orienting them are mainly used. In recent years, with the high-definition, high-brightness, large-scale, and thin-type screens, compared with existing products, polarizing films with fewer bad pixels and color spots and wide, long, and thin are required.
[0004] For the manufacturing method of polarizing film, for example, after the polyvinyl alcohol film is swollen with water (including warm water), it is dyed with iodine, stretched to arrange the iodine molecules, cross-linked with a cross-linking agent such as boric acid to maintain the stretched state, and dried to manufacture. The above-mentioned manufacture is carried out while the film is transported in a horizontal direction using a winder and a roller. In order to reduce the display bad points of the polarizing film, of course, the shortcomings of the polyvinyl alcohol film itself should be reduced, and it is also important to avoid the shortcomings such as scratches generated during the manufacture of the polarizing film. The above-mentioned scratches will not only become the display bad points of the polarizing film, but also produce color spots in the polarizing film when they occur in a wider area. It should be noted that the polarizing film in the present invention is also referred to as polarizing film and polarizer.
[0005] As a countermeasure to the scratches generated during the manufacture of polyvinyl alcohol-based films, a polyvinyl alcohol-based film having a dynamic friction coefficient of 0.03 or less for a stainless steel roller has been proposed (see Patent Document 1). In addition, as a countermeasure to the color spots generated during the manufacture of polarizing films, for example, a method for manufacturing polarizing films has been proposed in which the static friction coefficient of the roller in contact with the polyvinyl alcohol-based film is set within a specific range, thereby reducing wrinkles and uneven stretching (see Patent Document 2).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2006-188661
[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-17321 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, the disclosed technology of Patent Document 1 can reduce the scratches of the polyvinyl alcohol film itself, but cannot avoid the scratches generated during the manufacture of the polarizing film, which is still insufficient. In particular, when the polyvinyl alcohol film is in contact with the roller during the manufacture of the polarizing film, a large number of fine scratches are generated, so it is difficult to manufacture a large-area polarizing film.
[0012] The disclosed technology of Patent Document 2 can reduce the color spots of the polarizing film, but cannot avoid fine scratches, which is still insufficient. The above scratches are particularly noticeable in the manufacture of wide, thin and long polarizing films, and further improvement is sought.
[0013] It should be noted that the above-mentioned scratches are often several mm in length in the flow direction (MD direction) of the polarizing film, and usually scratches with a width of several microns or more and a depth of submicrons or more become a problem.
[0014] In addition, when scratches occur, shavings are generated. The shavings not only increase the defects of the polarizing film but also contaminate the production line of the polarizing film, causing a significant decrease in the production yield.
[0015] Therefore, in the present invention, under such background, there are provided a polyvinyl alcohol-based film capable of obtaining a polarizing film free of display defects and color spots, and a high-quality polarizing film using the polyvinyl alcohol-based film.
[0016] Solutions for solving problems
[0017] Therefore, in view of the above situation, the inventors of the present invention have repeatedly conducted in-depth research and found that by using a polyvinyl alcohol-based film having a specific film surface hardness in an indentation test in a microscopic area, it is less likely to be scratched when manufacturing a polarizing film, and a high-quality polarizing film without display bad spots or color spots can be obtained.
[0018] That is, the gist of the present invention is a polyvinyl alcohol-based film characterized in that the hardness of the film surface is 65 to 90 MPa when subjected to a nanoindentation test under the following conditions (1) to (3) in accordance with ISO14577:2002.
[0019] Conditions (1) Measurement environment: 25°C 50% RH
[0020] Condition (2) Indenter: Berkovich type (triangular pyramid, apex angle 65°, ε = 0.75, diamond)
[0021] Condition (3) Maximum indentation depth: 500nm
[0022] Moreover, the gist of the present invention is a polarizing film obtained by using the above-mentioned polyvinyl alcohol-based film.
[0023] Effects of the Invention
[0024] The polyvinyl alcohol-based film of the present invention can reduce scratches during the manufacture of polarizing films, and can obtain wide, long, and thin polarizing films without display bad spots or color spots. DETAILED DESCRIPTION
[0025] Hereinafter, the present invention will be described in detail.
[0026] The greatest feature of the polyvinyl alcohol film of the present invention is that the hardness of the film surface when subjected to a nanoindentation test under the following conditions (1) to (3) is 65 to 90 MPa.
[0027] Conditions (1) Measurement environment: 25°C 50% RH
[0028] Condition (2) Indenter: Berkovich type (triangular pyramid, apex angle 65°, ε = 0.75, diamond)
[0029] Condition (3) Maximum indentation depth: 500nm
[0030] In the nanoindentation test, test conditions other than those specified in conditions (1) to (3) may be performed in accordance with ISO 14577:2002 Metallic materials—Instrumented indentation test for hardness and materials parameters. Details of the measurement principle are described in Handbook of Micro Nano / Nano Tribology (CRC, ed. by Bharat Bharat Bhushan).
[0031] In the nanoindentation test implemented in the present invention, a tiny indenter is pressed into a tiny area with a tiny load, and the displacement relative to the load and the displacement when the load is slowly removed are measured, thereby calculating the hardness of the film surface and the elastic modulus of the film surface as an index of resilience. As a measurement standard, there is also JIS Z 2255:2003 Method for ultra-low loading hardness test, which can obtain similar data on surface hardness.
[0032] The polyvinyl alcohol-based film of the present invention can reduce scratches on rollers, but the occurrence of the scratches depends on the surface roughness of the rollers used for conveyance and stretching.
[0033] The above rollers are generally mirror-finished to a surface roughness Rz of less than 1μm, but even submicron-high protrusions on the surface can scratch the film. Therefore, a tiny indenter must be used to measure the properties of the film surface and adjust the optimal hardness and elastic modulus during polarizing film manufacturing.
[0034] As a method for measuring the properties of the film surface, generally, Brinell hardness, Rockwell hardness, Vickers hardness, etc., which are pressed into a larger indenter in a wider area with a larger load, can be cited. However, it is difficult to accurately evaluate using these methods, and the nanoindentation test implemented in the present invention is effective. It should be noted that the maximum value of the hardness of the film surface in the nanoindentation test is usually 10000MPa.
[0035] The hardness of the film surface of the polyvinyl alcohol-based film must be 65 to 90 MPa, preferably 68 to 85 MPa, and particularly preferably 70 to 80 MPa.
[0036] When the hardness of the film surface is lower than the lower limit, the scratches with the roller increase, and the purpose of the present invention cannot be achieved. On the contrary, when the hardness of the film surface exceeds the upper limit, the adhesion between the film and the roller decreases, the scratches increase, and the purpose of the present invention cannot be achieved.
[0037] The aspect of the present invention that is particularly worth mentioning is that, generally speaking, the harder the film surface is, the less likely it is to be scratched, but in fact, it must be softened to a degree that ensures close adhesion to the roller. When the film surface is too hard, the film simply slides on the roller and cannot be smoothly transported in accordance with the rotation of the roller, thus causing scratches. The above-mentioned scratches not only become display bad points of the polarizing film, but also tend to cause color spots in the polarizing film and polarizing plate when they occur over a wide range.
[0038] Furthermore, as a particularly noteworthy effect of the present invention, there can be mentioned a self-repairing function of scratches.
[0039] The self-repairing function is a function in which the polymer chains of the polyvinyl alcohol resin move to the concave part and flatten it. Although it is difficult to completely repair a deep concave part, shallow scratches with a depth of about submicron can be repaired. When the hardness of the surface of the polyvinyl alcohol film is lower than the above lower limit, deep scratches are easily generated, and therefore, self-repair cannot be achieved. However, when the softness is above the lower limit and close to the lower limit, an effective self-repairing function tends to be exhibited.
[0040] As a method for controlling the hardness of the surface of the polyvinyl alcohol film, there can be cited a method of appropriately adjusting the chemical structure and composition of the polyvinyl alcohol resin, the additives of the polyvinyl alcohol film, the manufacturing conditions, etc. Among them, a method of appropriately adjusting the manufacturing conditions of the polyvinyl alcohol film is preferred, and a method of appropriately adjusting the drying and heat treatment conditions is particularly preferred.
[0041] The polyvinyl alcohol film of the present invention preferably has an elastic modulus of 1.0 to 1.4 GPa, particularly preferably 1.05 to 1.35 GPa, and further preferably 1.1 to 1.3 GPa on the film surface when subjected to a nanoindentation test under the above conditions (1) to (3).
[0042] When the elastic modulus of the film surface is too low, deep scratches tend to be generated in the polarizing film manufacturing process and self-repair tends to be difficult to show. When it is too high, a large number of shallow scratches tend to be generated in the polarizing film manufacturing process.
[0043] Here, it is generally believed that the higher the elastic modulus of the film surface, the less likely it is to be scratched, but in fact, in order to flatten the depressions caused by the protrusions on the roller surface, a certain degree of low elastic modulus is preferred. In other words, the film surface must have a certain degree of buffering function.
[0044] The polyvinyl alcohol film of the present invention is produced using a polyvinyl alcohol resin as a raw material.
[0045] As the polyvinyl alcohol-based resin used in the present invention, a resin produced by saponifying an unmodified polyvinyl alcohol-based resin, i.e., polyvinyl acetate obtained by polymerizing vinyl acetate, is generally used. If necessary, a resin obtained by saponifying a copolymer of vinyl acetate and a small amount (usually less than 10 mol %, preferably less than 5 mol %) of a component copolymerizable with vinyl acetate may also be used. As components copolymerizable with vinyl acetate, for example, unsaturated carboxylic acids (e.g., including salts, esters, amides, nitriles, etc.), olefins having 2 to 30 carbon atoms (e.g., ethylene, propylene, n-butene, isobutylene, etc.), vinyl ethers, unsaturated sulfonates, etc. may be cited. In addition, a modified polyvinyl alcohol-based resin obtained by chemically modifying the hydroxyl group after saponification may also be used.
[0046] In addition, as the polyvinyl alcohol-based resin, a polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can also be used. The polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can be obtained, for example, by the following methods: (i) a method of saponifying a copolymer of vinyl acetate and 3,4-diacetoxy-1-butene; (ii) a method of saponifying and decarbonating a copolymer of vinyl acetate and vinyl ethylene carbonate; (iii) a method of saponifying and deketalizing a copolymer of vinyl acetate and 2,2-dialkyl-4-vinyl-1,3-dioxolane; (iv) a method of saponifying a copolymer of vinyl acetate and glycerol monoallyl ether.
[0047] The weight average molecular weight of the polyvinyl alcohol resin is preferably 100,000 to 300,000, particularly preferably 110,000 to 280,000, and further preferably 120,000 to 260,000. If the weight average molecular weight is too small, it is difficult to obtain sufficient optical properties when the polyvinyl alcohol resin is made into an optical film, and if it is too large, it is difficult to stretch the polyvinyl alcohol film into a polarizing film. It should be noted that the weight average molecular weight of the polyvinyl alcohol resin is the weight average molecular weight measured by the GPC-MALS method.
[0048] The average saponification degree of the polyvinyl alcohol resin used in the present invention is usually preferably 98 mol% or more, particularly preferably 99 mol% or more, further preferably 99.5 mol% or more, and particularly preferably 99.8 mol% or more. If the average saponification degree is too low, there is a tendency that sufficient optical properties cannot be obtained when the polyvinyl alcohol film is made into a polarizing film.
[0049] Here, the average saponification degree in the present invention is measured in accordance with JIS K 6726.
[0050] As the polyvinyl alcohol-based resin used in the present invention, two or more polyvinyl alcohol-based resins having different modified substances, modification amounts, weight average molecular weights, average saponification degrees, etc. may be used in combination.
[0051] The polyvinyl alcohol film of the present invention can be continuously manufactured as follows: a polyvinyl alcohol resin aqueous solution is prepared using the above-mentioned polyvinyl alcohol resin, the above-mentioned polyvinyl alcohol resin aqueous solution is discharged into a rotating casting mold and cast, and a film is formed and dried by a casting method, thereby being continuously manufactured, for example, it can be manufactured by the following steps.
[0052] In step (A), a film is formed by a casting method.
[0053] In step (B), the formed film is heated and dried, and heat-treated as necessary.
[0054] In step (C), both ends of the dried film are trimmed and then wound up on a roll.
[0055] Here, examples of the casting mold include a casting drum (drum-type roll) and an endless belt. From the viewpoint of widening, elongating, and excellent uniformity of film thickness, a casting drum is preferably used.
[0056] Hereinafter, the case where the casting mold is a casting drum will be described as an example.
[0057] First, the above-mentioned step (A) will be described.
[0058] In step (A), it is preferred that the polyvinyl alcohol resin is first washed with water and then dehydrated using a centrifuge or the like to form a polyvinyl alcohol resin wet cake having a water content of 50 wt % or less. If the water content is too high, it tends to be difficult to form an aqueous solution of a desired concentration.
[0059] The polyvinyl alcohol-based resin wet cake is dissolved in warm water or hot water to prepare a polyvinyl alcohol-based resin aqueous solution.
[0060] The method for preparing the aqueous solution of the polyvinyl alcohol resin is not particularly limited. For example, it can be prepared using a heated multi-screw extruder. In addition, the aforementioned polyvinyl alcohol resin wet cake is placed in a dissolution tank equipped with upper and lower circulating flow generating stirring blades, and water vapor is blown into the tank to dissolve and prepare an aqueous solution of the desired concentration.
[0061] From the viewpoint of the film forming property of the polyvinyl alcohol film, the polyvinyl alcohol resin aqueous solution preferably contains, in addition to the polyvinyl alcohol resin, a generally used plasticizer such as glycerol, diglycerol, triglycerol, ethylene glycol, triethylene glycol, polyethylene glycol, trimethylolpropane, and a surfactant including at least one of nonionic, anionic, and cationic. The content of the plasticizer such as glycerol and the surfactant is preferably 1 to 20% by weight, more preferably 5 to 15% by weight, relative to the polyvinyl alcohol resin.
[0062] The resin concentration of the polyvinyl alcohol-based resin aqueous solution thus obtained is preferably 15 to 60% by weight, particularly preferably 17 to 55% by weight, and further preferably 20 to 50% by weight. When the resin concentration of the aqueous solution is too low, the drying load becomes large, thereby tending to reduce productivity, and when it is too high, the viscosity becomes too high, tending to be difficult to dissolve uniformly.
[0063] Next, the obtained polyvinyl alcohol-based resin aqueous solution is subjected to a degassing treatment. As the degassing method, there can be mentioned methods such as static degassing and degassing using a multi-screw extruder equipped with a vent. As the multi-screw extruder equipped with a vent, a twin-screw extruder equipped with a vent is generally used.
[0064] After the degassing treatment, a certain amount of the polyvinyl alcohol-based resin aqueous solution was introduced into a T-slit die one by one, discharged onto a rotating casting drum, and cast to form a film by a casting method.
[0065] The temperature of the polyvinyl alcohol-based resin aqueous solution at the outlet of the T-slit die is preferably 80 to 100°C, particularly preferably 85 to 98°C.
[0066] When the temperature of the polyvinyl alcohol-based resin aqueous solution is too low, the fluidity tends to be poor, and when it is too high, the solution tends to foam.
[0067] The viscosity of the polyvinyl alcohol-based resin aqueous solution when discharged is preferably 50 to 200 Pa·s, particularly preferably 70 to 150 Pa·s.
[0068] When the viscosity of the aqueous solution is too low, the fluidity tends to be poor, and when it is too high, casting tends to be difficult.
[0069] The discharge speed of the polyvinyl alcohol-based resin aqueous solution discharged from the T-slit die to the casting drum is preferably 0.2 to 5 m / min, particularly preferably 0.4 to 4 m / min, and further preferably 0.6 to 3 m / min.
[0070] When the discharge speed is too slow, productivity tends to decrease, and when it is too fast, casting tends to become difficult.
[0071] The diameter of the casting drum is preferably 2 to 5 m, particularly preferably 2.4 to 4.5 m, and further preferably 2.8 to 4 m.
[0072] If the diameter is too small, the drying length tends to be insufficient and the speed tends to be difficult to achieve, while if it is too large, the conveying performance tends to decrease.
[0073] The width of the casting drum is preferably 4 m or more, particularly preferably 4.5 m or more, further preferably 5 m or more, and particularly preferably 5 to 6 m.
[0074] If the width of the casting drum is too small, productivity tends to decrease.
[0075] The rotation speed of the casting drum is preferably 3 to 50 m / min, particularly preferably 4 to 40 m / min, and further preferably 5 to 35 m / min.
[0076] When the rotation speed is too slow, productivity tends to decrease, and when it is too fast, the releasability from the casting drum tends to decrease.
[0077] The surface temperature of the casting drum is preferably 40 to 99°C, particularly preferably 60 to 95°C.
[0078] When the surface temperature is too low, the releasability from the casting roll tends to decrease, and when it is too high, foaming tends to occur.
[0079] Next, the step (B) is described. The step (B) is a step of heating and drying the film after film formation.
[0080] The film formed by the casting drum can be dried by contacting the surface and back of the film alternately with a plurality of metal heating rollers. The surface temperature of the metal heating roller is usually 40 to 150°C, preferably 50 to 130°C, and particularly preferably 60 to 110°C. If the surface temperature is too low, the film tends to be poorly dried, and if it is too high, the film tends to be over-dried and have poor appearance such as bending. In addition, the metal heating roller is preferably a roller with a diameter of 0.2 to 2 m, the surface of which is hard chrome-plated or mirror-finished, and 2 to 30 rollers, preferably 10 to 25 rollers, are usually used for drying.
[0081] In the present invention, it is preferred that the film is heat treated after being dried using a metal heating roller. The heat treatment temperature is preferably 60 to 150° C., particularly preferably 70 to 140° C. When the heat treatment temperature is too low, the water resistance of the polyvinyl alcohol film is insufficient or it tends to be a cause of phase difference deviation. When the heat treatment temperature is too high, the stretchability during the manufacture of the polarizing film tends to decrease. Examples of the heat treatment method include a method using a floating dryer, a method of irradiating near-infrared rays on both sides of the film using an infrared lamp, and the like.
[0082] The film that has been dried and, if necessary, heat-treated is passed through the above step (C) to become a product (polyvinyl alcohol film of the present invention). Step (C) is a step of trimming both ends of the film and winding it up on a roll.
[0083] It should be noted that, so far, a method for preparing a polyvinyl alcohol resin aqueous solution, casting the aqueous solution on a rotating casting drum (drum-type roll), and forming a film by a casting method and drying it to produce a polyvinyl alcohol film has been described, but the polyvinyl alcohol resin aqueous solution can also be cast on a resin film or a metal belt to form a film and dry it.
[0084] From the perspective of thinning the polarizing film, the thickness of the polyvinyl alcohol film is preferably 5 to 60 μm, and from the perspective of further thinning, it is particularly preferably 5 to 45 μm. From the perspective of avoiding breakage and the relationship between the characteristics of the present invention (hardness of the film surface) and thinning, it is further preferably 10 to 45 μm.
[0085] The width of the polyvinyl alcohol film is preferably 4 m or more, more preferably 4.5 m or more from the viewpoint of increasing the area, and particularly preferably 4.5 to 6 m from the viewpoint of avoiding breakage.
[0086] The length of the polyvinyl alcohol film is preferably 4 km or longer, more preferably 4.5 km or longer from the viewpoint of increasing the area, and particularly preferably 4.5 to 50 km from the viewpoint of transport weight.
[0087] The polyvinyl alcohol-based film of the present invention has appropriate hardness and is suitable for use as a polyvinyl alcohol-based film for optical use, and is particularly preferably used as a raw roll for a polarizing film.
[0088] Hereinafter, a method for producing a polarizing film using the polyvinyl alcohol-based film of the present invention will be described.
[0089] The polarizing film of the present invention is produced by unwinding the polyvinyl alcohol-based film from a roll and conveying it in a horizontal direction, and then subjecting it to steps such as swelling, dyeing, boric acid cross-linking, stretching, washing, and drying.
[0090] The swelling process is implemented before the dyeing process. The swelling process can not only clean the pollutants on the surface of the polyvinyl alcohol film, but also has the effect of preventing uneven dyeing by swelling the polyvinyl alcohol film. In the swelling process, water is usually used as the treatment liquid. The treatment liquid only needs to be water as the main component, and a small amount of additives such as iodide, surfactant, alcohol, etc. can also be added. The temperature of the swelling bath is usually around 10 to 45°C, and the immersion time in the swelling bath is usually around 0.1 to 10 minutes. In addition, stretching operation can also be performed during the treatment as needed.
[0091] The dyeing process is carried out by contacting the film with a liquid containing iodine or a dichroic dye. An aqueous solution of iodine-potassium iodide is usually used, and it is appropriate that the concentration of iodine is 0.1 to 2 g / L and the concentration of potassium iodide is 1 to 100 g / L. It is practical to dye for about 30 to 500 seconds. The temperature of the treatment bath is preferably 5 to 50° C. In addition to the aqueous solvent, the aqueous solution may also contain a small amount of an organic solvent compatible with water. In addition, a stretching operation may be performed during the treatment as required.
[0092] The boric acid crosslinking process is carried out using a boron compound such as boric acid or borax. The boron compound is used in the form of an aqueous solution or a water-organic solvent mixture at a concentration of about 10 to 100 g / L. From the perspective of stabilizing the polarization performance, it is preferred that potassium iodide coexists in the liquid. Preferably, the temperature during the treatment is about 30 to 70° C., the treatment time is about 0.1 to 20 minutes, and a stretching operation can be performed during the treatment as needed.
[0093] The stretching process is preferably stretched 3 to 10 times, preferably 3.5 to 6 times, in a uniaxial direction. At this time, some stretching can also be performed in a direction perpendicular to the stretching direction (to prevent shrinkage in the width direction, or stretching above this degree). The temperature during stretching is preferably 30 to 170°C. Furthermore, as long as the stretching ratio is finally set to the aforementioned range, the stretching operation can be implemented not only in one stage, but also in any stage of the manufacturing process.
[0094] The cleaning process is carried out, for example, by immersing the polyvinyl alcohol film in an aqueous iodide solution such as water or potassium iodide, so that the precipitate produced on the surface of the film can be removed. When using an aqueous potassium iodide solution, the concentration of potassium iodide can be about 1 to 80 g / L. The temperature during the cleaning treatment is usually 5 to 50° C., preferably 10 to 45° C. The treatment time is usually 1 to 300 seconds, preferably 10 to 240 seconds. It should be noted that water cleaning and cleaning with an aqueous potassium iodide solution can also be appropriately combined.
[0095] The drying step may be performed in the air at 40 to 80° C. for 1 to 10 minutes.
[0096] The polarization degree of the polarizing film is preferably 99.5% or more, more preferably 99.8% or more. If the polarization degree is too low, the contrast in the liquid crystal display tends to be unable to be ensured.
[0097] In addition, the degree of polarization is generally determined by measuring the light transmittance (H) at a wavelength λ in a state where two polarizing films are stacked so that their orientation directions are in the same direction. 11 ), and the transmittance (H1) measured at a wavelength λ when two polarizing films are overlapped in such a way that their orientation directions are orthogonal to each other, are calculated according to the following formula.
[0098] 〔(H 11 -H1) / (H 11 +H1)〕 1 / 2
[0099] Furthermore, the single-unit transmittance of the polarizing film of the present invention is preferably 42% or more. If the single-unit transmittance is too low, it tends to be impossible to achieve high brightness of a liquid crystal display.
[0100] The single-piece transmittance is a value obtained by measuring the light transmittance of a single polarizing film using a spectrophotometer.
[0101] In this way, the polarizing film of the present invention can be obtained. The polarizing film of the present invention is suitable for manufacturing a polarizing plate without display defective pixels or color spots.
[0102] Hereinafter, the method for producing the polarizing plate of the present invention will be described.
[0103] The polarizing film of the present invention is bonded with an optically isotropic resin film as a protective film on one or both sides thereof by means of an adhesive, thereby forming a polarizing plate. Examples of the protective film include films or sheets of cellulose triacetate, cellulose diacetate, polycarbonate, polymethyl methacrylate, cycloolefin polymer, cycloolefin copolymer, polystyrene, polyether sulfone, polyarylene ester, poly-4-methylpentene, polyphenylene ether, and the like.
[0104] The lamination can be performed by a known method, for example, by uniformly applying a liquid adhesive composition to the polarizing film, the protective film, or both, laminating and pressing the two together, and then heating or irradiating with active energy rays.
[0105] In order to reduce the thickness of the polarizing film, a curable resin such as urethane resin, acrylic resin, or urea resin may be applied to one or both sides of the polarizing film instead of the protective film and cured to form a polarizing plate.
[0106] The polarizing film and polarizing plate obtained according to the present invention have no display bad pixels and color spots, and are preferably used in: liquid crystal display devices of mobile information terminals, personal computers, televisions, projectors, signs, electronic desktop computers, electronic clocks, word processors, electronic paper, game consoles, video recorders, cameras, photo albums, thermometers, audio equipment, automobiles, mechanical measuring instruments, etc., sunglasses, anti-glare glasses, stereo glasses, wearable displays, anti-reflection layers for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication equipment, medical equipment, building materials, toys, etc.
[0107] Example
[0108] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the invention is exceeded.
[0109] In addition, in an example, "%" means a weight basis.
[0110] Each physical property was measured as follows.
[0111] <Measurement conditions>
[0112] (1) Film surface hardness (MPa), film surface elastic modulus (GPa)
[0113] A 1cm×1cm test piece was cut out from the obtained polyvinyl alcohol film, and the state was adjusted at 25°C 50% RH for 1 day before the test. Then, a nano indentation tester "Triboindenter" manufactured by Hysitron was used as a test machine, and a triangular pyramid indenter called Berkovich type (vertex angle 65°, ε=0.75, diamond) was used as an indenter. The test was carried out under an environment of 25°C 50% RH. The test was carried out on both sides of the film and the average value was taken. It should be noted that before the test, fused quartz (hardness 9250MPa, elastic modulus 69.6GPa) was used as a standard sample to obtain a correction coefficient for calculating the projection area A of the indenter on the sample during indentation.
[0114] The nanoindentation test is as follows: First, the indenter is placed vertically in contact with the surface of the test piece, and a load is slowly applied at an indentation speed of 100 nm / sec. Then, the indentation is stopped when the maximum indentation depth reaches 500 nm, and the load is slowly restored to zero at a withdrawal speed of 100 nm / sec.
[0115] The maximum load P (N) and the projected area A (mm) of the indenter obtained from the above test are 2 ), and calculate the hardness (MPa) of the film surface according to the following formula (A).
[0116] (Formula A) Hardness of film surface = P / A
[0117] In addition, the slope S (N / mm) of the tangent line at the maximum load is obtained from the unloading displacement curve. The slope S (N / mm) and the projection area A (mm 2 ), and calculate the elastic modulus (GPa) of the film surface according to the following formula (B).
[0118] (Formula B) Elastic modulus of film surface = 0.001×(S×π 1 / 2 ) / (2×A 1 / 2 )(π is the ratio of circumference to diameter)
[0119] (2) Abrasions
[0120] Ten test pieces of 1 cm×1 cm were cut out from the obtained polarizing film and the presence of scratches of 10 μm or more in width were observed using a laser focus microscope VK-9700 manufactured by KEYENCE (objective lens: 50 times) and evaluated based on the following criteria.
[0121] (Evaluation Criteria)
[0122] ○···All the test pieces had no scratches.
[0123] △···One of the test pieces is scratched.
[0124] ×···All test pieces were scratched.
[0125] (3) Display bad pixels (number)
[0126] A test piece of 30 cm in length and 13 cm in width was cut out from the obtained polarizing film, and visual inspection was performed under an environment of 15000 lx to measure the number of display defective pixels of 100 μm or more.
[0127] (4) Pigmentation
[0128] A test piece of 30 cm in length and 13 cm in width was cut out from the obtained polarizing film and clamped between two polarizing plates in a crossed prism state (single-body transmittance 43.5%, polarization degree 99.9%) at an angle of 45°. The optical color spots were observed in transmission mode using a light source box with a surface illumination of 14000 lx and evaluated according to the following criteria.
[0129] ○···No color spots.
[0130] △···Slight stains.
[0131] ×···There are stains.
[0132] <Example 1>
[0133] (Manufacture of polyvinyl alcohol-based films)
[0134] 1000 kg of a polyvinyl alcohol resin with a weight average molecular weight of 142,000 and a saponification degree of 99.8 mol%, 2500 kg of water, and 100 kg of glycerol as a plasticizer were added, and the temperature was raised to 140°C while stirring, and the concentration was adjusted to a resin concentration of 25%, thereby obtaining a uniformly dissolved polyvinyl alcohol resin aqueous solution. Next, the polyvinyl alcohol resin aqueous solution was supplied to a twin-screw extruder equipped with an exhaust port for degassing, and then the aqueous solution temperature was set to 90°C, and discharged from a T-slit die outlet to a rotating casting drum and cast to form a film. The film was peeled off from the casting drum, and the surface and back of the film were alternately contacted with multiple metal heating rollers (maximum temperature 86°C) while being dried so that the water content of the film was less than 10%. Furthermore, a floating dryer was used to blow hot air at 133°C from both sides of the film to dry the film until the moisture content of the film became 2%, and both ends were trimmed and rolled up on a roll to obtain a polyvinyl alcohol film with a width of 4.8 m, a thickness of 45 μm, and a length of 5 km. The properties of the obtained polyvinyl alcohol film are shown in Table 1.
[0135] (Manufacturing of polarizing film)
[0136] The obtained polyvinyl alcohol film was conveyed in the horizontal direction using a conveyor roller. First, it was immersed in a water tank at a water temperature of 25°C to swell it while stretching it to 1.7 times in the flow direction. Next, it was immersed in an aqueous solution containing 0.5 g / L iodine and 30 g / L potassium iodide at 28°C for dyeing while stretching it to 1.6 times in the flow direction. Next, it was immersed in an aqueous solution (55°C) composed of 40 g / L boric acid and 30 g / L potassium iodide for boric acid crosslinking while uniaxially stretching it to 2.1 times in the flow direction. Finally, it was washed with an aqueous potassium iodide solution and then dried at 60°C for 2 minutes to obtain a polarizing film with a total stretch ratio of 5.7 times. The properties of the obtained polarizing film are shown in Table 1.
[0137] <Examples 2, 3, Comparative Examples 1, 2>
[0138] A polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1 except that the production was carried out under the conditions shown in Table 1. The properties of the obtained polyvinyl alcohol-based film and polarizing film are shown in Table 1.
[0139] [Table 1]
[0140]
[0141] It can be seen that for the polyvinyl alcohol films of Examples 1 to 3, the hardness of the film surface in the nanoindentation test is within the specific range of the present invention, and therefore, a polarizing film with fewer scratches can be obtained. However, for the polarizing film using the polyvinyl alcohol films of Comparative Examples 1 and 2, the hardness of the polyvinyl alcohol film surface is outside the specific range of the present invention, resulting in more scratches.
[0142] Furthermore, it was found that Examples 1 to 3 were better than Comparative Examples 1 and 2 in terms of the evaluation of display defects and color irregularities of the polarizing films obtained from the respective polyvinyl alcohol-based films.
[0143] The above embodiments show specific aspects of the present invention, but the above embodiments are merely examples and are not to be construed as limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention.
[0144] Industrial Applicability
[0145] The polarizing film and polarizing plate obtained by the present invention have no display bad spots and color spots, and have excellent in-plane uniformity of polarization performance. They are preferably used in: mobile information terminals, personal computers, televisions, projectors, signs, electronic desktop computers, electronic clocks, word processors, electronic paper, game consoles, video recorders, cameras, photo albums, thermometers, audio equipment, automobiles, liquid crystal display devices of mechanical measuring instruments, sunglasses, anti-glare glasses, stereo glasses, wearable displays, anti-reflection layers for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication equipment, medical equipment, building materials, toys, etc.
Claims
1. A polyvinyl alcohol film, characterized in that: According to ISO14577:2002, when a nanoindentation test is performed under the following conditions (1) to (3), the hardness of the film surface is 65 to 90 MPa and the elastic modulus of the film surface is 1.0 to 1.4 GPa, and the thickness of the polyvinyl alcohol-based film is 5 to 45 μm. The polyvinyl alcohol film is manufactured by the following steps: Step (A) is to form a film by casting using a casting roll having a surface temperature of 40 to 99°C. Step (B), drying the formed film by contacting it with a metal heating roller, and then performing a heat treatment, wherein when the heat treatment temperature is higher than the maximum temperature of the metal heating roller, the temperature difference between them is set to 46°C or more, or when the heat treatment temperature is lower than the maximum temperature of the metal heating roller, the temperature difference between them is set to 32°C or more, Step (C), trimming both ends of the dried film and winding it on a roll, Conditions (1) Measurement environment: 25°C 50% RH Condition (2) Indenter: Berkovich type, triangular pyramid, apex angle 65°, ε = 0.75, diamond Condition (3) Maximum indentation depth: 500 nm.
2. A polarizing film, characterized in that: This is obtained by using the polyvinyl alcohol-based film according to claim 1.
Citation Information
Patent Citations
Manufacturing method for polarizing film
JP2004017321A
Polyvinyl alcohol film and method for producing the same
JP2006188661A
Manufacturing method for vinyl alcohol polymer film, and polarizing film
JP2003170456A
Polyvinyl alcohol-based film for optical use and polarizing film, polarizing plate
JP2006233179A